2021
DOI: 10.3390/polym13213668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(acrylamide-acrylic acid) on the Fire Resistance and Anti-Aging Properties of Transparent Flame-Retardant Hydrogel Applied in Fireproof Glass

Abstract: Poly(acrylamide-acrylic acid) (P(AM-co-AA)) was synthesized via the copolymerization of acrylamide and acrylic acid and well characterized by Fourier transform infrared spectroscopy. Afterward, the obtained P(AM-co-AA) was blended with flame retardants to prepare transparent flame-retardant hydrogel applied in the fireproof glass. The influence of poly(acrylamide-acrylic acid) on fire resistance and anti-aging properties of the transparent flame-retardant hydrogels were studied by assorted analysis methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When the test temperature rises to 350 °C, the polyacrylamide main chain depolymerizes into imide, acrylonitrile, and CO 2 , accompanied by the formation of a molten carbon layer. Compared to PAM-D hydrogel, the PAM/GO 1.4 /Ni 21.4 -D hydrogel exhibits less mass loss in the first stage, which is attributed to the greater difficulty of volatilizing physically bound water and dehydrating hydroxyl groups compared to free water . This phenomenon can be explained by the fact that the introduction of −NH 2 and GO interaction the hydrogel’s water retention properties, resulting in excellent thermal stability and carbonization efficiency …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the test temperature rises to 350 °C, the polyacrylamide main chain depolymerizes into imide, acrylonitrile, and CO 2 , accompanied by the formation of a molten carbon layer. Compared to PAM-D hydrogel, the PAM/GO 1.4 /Ni 21.4 -D hydrogel exhibits less mass loss in the first stage, which is attributed to the greater difficulty of volatilizing physically bound water and dehydrating hydroxyl groups compared to free water . This phenomenon can be explained by the fact that the introduction of −NH 2 and GO interaction the hydrogel’s water retention properties, resulting in excellent thermal stability and carbonization efficiency …”
Section: Resultsmentioning
confidence: 99%
“…Compared to PAM-D hydrogel, the PAM/GO 1.4 /Ni 21.4 -D hydrogel exhibits less mass loss in the first stage, which is attributed to the greater difficulty of volatilizing physically bound water and dehydrating hydroxyl groups compared to free water. 35 This phenomenon can be explained by the fact that the introduction of −NH 2 and GO interaction the hydrogel's water retention properties, resulting in excellent thermal stability and carbonization efficiency. 36 Figure 7b shows a schematic diagram of the PAM/GO 1.4 /Ni 22.4 hydrogel burning under an alcohol lamp.…”
Section: Mechanical Behavior Of Pam/go/ni Composite Hydrogelsmentioning
confidence: 99%
“…6 Wang et al have observed an enhancement in fire resistance and anti-aging property of polyacrylamide hydrogel by introducing acrylic acid and methacrylic acid, respectively. 7,8 Chen et al revealed that the addition of ammonium polyphosphate to shear stiffening gel can provide effective impact resistance and fire resistance. 9 In summary, the construction of the interpenetrating polymer network can bring high stability to hydrogels, but there are few reports of their application to fireproof glass.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al found that hydrogels formed by acrylamide, acrylic acid and water glass can effectively improve their water retention and compression resistance 6 . Wang et al have observed an enhancement in fire resistance and anti‐aging property of polyacrylamide hydrogel by introducing acrylic acid and methacrylic acid, respectively 7,8 . Chen et al revealed that the addition of ammonium polyphosphate to shear stiffening gel can provide effective impact resistance and fire resistance 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to enhance the fire resistance of transparent flame-retarded hydrogels via chemical modification of hydrogel network and physical adding flame retardants. Ammonium polyphosphate (APP), ammonium dihydrogen phosphate (ADP), ammonium hydrogen phosphate and other phosphorus-based flame retardants are widely used in the field of flame-retarded hydrogels to protect the hydrogel from burning [7]. Zheng et al introduced basalt fibers and ammonium polyphosphate (APP) into polyacrylamide hydrogels to improve the fire resistance properties and found that APP can effectively delay the thermal decomposition process of the hydrogel by forming an expanded char layer [8].…”
Section: Introductionmentioning
confidence: 99%